Sistem Informasi Penjualan Berbasis Web pada Toko Arifin Menggunakan Metode Rapid Application Development (RAD) - muhammad hapidz awabin; Surtikanti (CV. Multi Kreasi Media, 2022)
The rapid development of a trading business or industry at this time makes information a very important role in supporting the course of sales operations. At the Arifin Store which is engaged in industry which was established in 2010 it is still done conventionally, therefore an online sales system is designed using sales promotion media with the aim of increasing sales volume so that store revenue increases. The method used in this research is Rapid Application Development (RAD) because the application developed is a simple application and does not require a long time to develop. Because the RAD method supports designing applications in a short period of time. From this research resulted in a Web-Based Sales Information System application at the Arifin Store using the UML design which was developed using the PHP and MySQL programming languages as the database server, as well as the Black Box as a testing medium so that it can make it easier for consumers and the Arifin Store to view and review product and sales reports. Keywords: information Systems, Sale, Rapid Application Development (RAD)